2020
DOI: 10.3389/fvets.2020.577466
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Severe Microfilaremia in Four Dogs Naturally Infected With Dirofilaria repens as the Primary Disease or a Disease Complicating Factor

Abstract: Subcutaneous dirofilariosis in dogs, caused by Dirofilaria repens, is an underdiagnosed disease, now recognized for its zoonotic potential, and growing distribution and prevalence across Europe and Asia. Our understanding of the pathogenicity in human and canine host remains unclear, but case reports suggest that microfilariae (Mf) as well as adult D. repens may directly cause internal organs damage or may be a factor complicating the course of other ailments. The purpose of the study was to report high Mf in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…On the contrary to this, D. repens infestation is often asymptomatic [ 53 ]. However, fatal outcomes of this diseases were observed in D. repens infestation, due to the massive release of the filarial endosymbiotic bacterium Wolbachia after microfilaricidal treatment [ 54 ]. Hence, in order to avoid fatal outcomes, these complications of antifilarial treatment have to be carefully considered while treating dirofilariasis [ 50 , 51 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary to this, D. repens infestation is often asymptomatic [ 53 ]. However, fatal outcomes of this diseases were observed in D. repens infestation, due to the massive release of the filarial endosymbiotic bacterium Wolbachia after microfilaricidal treatment [ 54 ]. Hence, in order to avoid fatal outcomes, these complications of antifilarial treatment have to be carefully considered while treating dirofilariasis [ 50 , 51 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that D. repens infection leads to anemia and a state of chronic stress response that likely affects antibodies' production 35 . It has also been reported that high micro laremia develops in dogs with immunode ciency-related conditions 36 . On the contrary, in dogs infected with Brugia pahangi, the IgG levels speci c for adult worm extract were highest in amicro laremic dogs 37 .…”
Section: Discussionmentioning
confidence: 93%
“…A blood smear revealed the presence of Dirofilaria repens microfilariae in the patient. In this dog, Dirofilaria repens infection was likely associated with underlying immunodeficiency, which may have predisposed susceptibility to parasitic infection (22).…”
Section: Case History and Diagnostic Testingmentioning
confidence: 86%